The Chinese mega-project "One Belt, One Road" in the Central Asian region: geopolitical rhetoric and prospects for implementation - R. Kh. Akimov; A. K. Magomedov (Современная наука и инновации)
The Chinese infrastructure project "One Belt, One Road" worth $1 trillion has significant landscape, socio-economic and political consequences for the Central Asian states through which it runs. This article explores how the Chinese initiative has an impact on the local infrastructure and local communities of the region. The implementation of the project in the Central Asian states shows not only the strengths of the Chinese program, but highlights its shortcomings of yesterday, current risks and potential prospects. The explanatory concept "hierarchical realism" is used in the work, which allowed us to get closer to a better understanding of the difficulties in the implementation of the Chinese megaproject "One Belt, One Road". This concept helps us to reveal the existence in the past of Beijing's hierarchical view of the international system, according to which China plays a much more dominant role than it is expressed in China's official rhetoric. It was the elements of the hegemonic style in the implementation of the megaproject "One Belt, One Road" in the countries of Central Asia that led to the fact that Chinese plans were met here very coolly at first. The authors analyze the historical turn in the implementation of the Chinese megaproject, which is associated with the implementation of the Xi'an Declaration. The pioneering nature of the decisions taken at this summit in May 2023 consisted in their humanitarian and social orientation in order to overcome Beijing's previous hierarchical view of the Central Asian region.